When the Phoenicians Were Swedish: Rudbeck’s Atlantica and Phoenician Studies. - Burman, Annie; Boyes, Philip J. (Journal of the American Oriental Society)
Olof Rudbeck’s Atlantica (1679–1702) is a characteristically wide-ranging example of Early Modern scholarship in which the author draws on a compendious assortment of evidence to argue that his native Sweden was the cradle of human civilization. Within this discussion, he devotes particular attention to the Phoenicians, whom he attempts to paint as descendants of “Scythians” who had migrated to the Mediterranean from an original Swedish homeland. Drawing upon the work of earlier Phoenician scholars such as Joseph Scaliger and Samuel Bochart, as well as his own, often rather creative, etymologies, he seeks to demonstrate a relationship between the Phoenician language and Swedish. This paper explores how Rudbeck engages with and utilizes the Phoenician people and the Phoenician language in service of his wider proto-nationalist goals and places his work within the wider context of Phoenician studies in Early Modern Europe, a few decades before Barthélemy’s decipherment of the Phoenician script (1758). While clearly wrong in many of his conclusions, Rudbeck’s work can tell us much about perceptions of Phoenicians at an important time of transition between Renaissance scholarship and the beginnings of modern archaeological and linguistic research.